A broadband excursus through stellar afterlife - Olmi, Barbara; Morlino, Giovanni; Bucciantini, Niccolò (Il Colle di Galileo, 2025)
The workshop drew experts from the Supernova Remnants, Pulsars and Pulsar Wind Nebulae communities, both from a multi-wavelengths observational point of view and a theoretical perspective. Recent developments in these fields were discussed, with broader coverage of the related physical processes (such as acceleration and propagation of particles, relevance of the sources for Galactic Cosmic Rays). Particular attention was also devoted to statistical methods in astrophysics. The workshop also provided an opportunity to celebrate the career of Rino Bandiera who successfully dedicated most of his career to the aforementioned matters and retired this year.